Aerosol depolarization ratio at 1565nm in Finland with Halo Doppler lidar - Le, Viet (Helsingin yliopisto, 2021)
Atmospheric aerosol particles absorb and scatter solar radiation, directly altering the Earth’s radiation budget. These particles also have a complex role in weather and climate by changing cloud physical properties such as reflectivity by acting as cloud condensation nuclei or ice nuclei. Aerosol particles in the boundary layer are important because they pose a negative impact on air quality and human health. In addition, elevated aerosol from volcanic dust or desert dust present an imminent threat to aviation safety. To improve our understanding of the role of aerosol in influencing climate and the capability to detect volcanic ash, a ground-based network of Halo Doppler lidars at a wavelength of 1565 nm is used to collect data of atmospheric vertical profiles across Finland. By comparing the theoretical values of depolarization ratio of liquid clouds with the observed values, bleed through of each lidar is detected and corrected to improve data quality. The background noise levels of these lidars are also collected to assess their stability and durability. A robust classification algorithm is created to extract aerosol depolarization ratios from the data to calculate overall statistics. This study finds that bleed through is at 0.017 ± 0.0072 for the Uto-32 lidar and 0.0121 ± 0.0071 for the Uto-32XR lidar. By examining the time series of background noise level, these instruments are also found to be stable and durable. The results from the classification algorithm show that it successfully classified aerosol, cloud, and precipitation even on days with high turbulence. Depolarization ratios of aerosol across all the sites are extracted and their means are found to be at 0.055 ± 0.076 in Uto, 0.076 ± 0.090 in Hyytiala, 0.076 ± 0.071 in Vehmasmaki and 0.041 ± 0.089 in Sodankyla. These mean depolarization ratios are found to vary by season and location. They peak during summer, when pollen is abundant, but they remain at the lowest in the winter. As Sodankylä is located in the Artic, it has aerosols with lower ...